Do vivido ontem ao realizado hoje: marcas que reverberam na ação docente - Correa, Ana Claudia Esteves (2020)
The general objective of this work is to analyze how experiences lived by teachers, while they were students, reverberate in their professional performance and teaching development in their own speeches. The specific objectives were to identify situations lived by teachers which marked their lives as students; to verify how such situations made the relations teacher-student-knowledge more difficult or easier when they became teachers; to problematize the critical incidents present in the teachers’ narratives and analyze them as formative strategy. These objectives are justifiable due to the need for the design of teacher development proposals that are aligned with the real needs of the teachers and that include elements of their life experiences as thematic possibilities. The search for answers to the initial questions occurred through a qualitative approach. The production of information happened by means of the collection of individual accounts shared in a teachers’ meeting, besides reflective interviews with five teachers who teach the final years of Middle School in a private school in the city of São Paulo. The choice of the reflective interview as one of the strategies for the production of information was due to the possibility of interaction between the interviewer and the interviewee that this tool carries in itself. The information produced in these interviews was later analyzed and organized in thematic branches. The main theoretical references used were Wallon (1986a, 1986b, 1975, 2007), Almeida (2009, 2012, 2015, 2019), Imbernón (2010), Placco (2010), Puig (2007), Vinha (2009, 2016) and Zaragaza (2006). It was realized that the use of critical incidents to support the production of formative proposals had positive results as, by means of accounts of memorable episodes in their lives as students, the teachers had the opportunity to rethink the meaning of the lived experience in a new perspective and, therefore, exercise self knowledge as well as better understand the importance of his/her role in the interpersonal relations in the educational process. Another evidence was articulating the formative proposals with the teachers’ needs and, mainly, their own lived path, will enable them to gain repertoire and knowledge about possibilities of action that open space for the holistic development of all of those involved in the teaching-learning process